The single-molecule electrical conductance of a rotaxane-hexayne supramolecular assembly. - Milan, D; Krempe, M; Ismael, A; Movsisyan, L; Franz, M; Grace, I; Brooke, R; Schwarzacher, W; Higgins, S; Anderson, H; Lambert, C; Tykwinski, R; et al. (Royal Society of Chemistry, 2016)
Oligoynes are archetypical molecular wires due to their 1-D chain of conjugated carbon atoms and ability to transmit charge over long distances by coherent tunneling. However, the stability of the oligoyne can be an issue. Here we address this problem by two stabilization methods, namely sterically shielding endgroups, and rotaxination to produce an insulated molecular wire. We demonstrate the threading of a hexayne within a macrocycle to form a rotaxane and report measurements of the electrical conductance of this single supramolecular assembly within an STM break junction. The macrocycle is retained around the hexayne through the use of 3,5-diphenylpyridine stoppers at both ends of the molecular wire, which also serve as chemisorption contacts to the gold electrodes of the junction. Molecular conductance was measured for both the supramolecular assembly and also for the molecular wire in the absence of the macrocycle. The threaded macrocycle, which at room temperature is mobile along the length of the hexayne between the stoppers, has only a minimal impact on the conductance. However, the probability of molecular junction formation in a given break junction formation cycle is notably lower with the rotaxane. In seeking to understand the conductance behavior, the electronic properties of these molecular assemblies and the electrical behavior of the junctions have been investigated by using DFT-based computational methods.